Characterization of HIV-1 Infection and Innate Sensing in Different Types of Primary Human Monocyte-Derived Macrophages - Elisabeth A. Diget; Kaja Zuwala; Randi K. Berg; Rune R. Laursen; Stine Søby; Lars Østergaard; Jesper Melchjorsen; Trine H. Mogensen (Mediators of Inflammation)
Macrophages play an important role in human immunodeficiency virus (HIV) pathogenesis and contribute to establishment of a viral reservoir responsible for continuous virus production and virus transmission to T cells. In this study, we investigated the differences between various monocyte-derived macrophages (MDMs) generated through different differentiation protocols and evaluated different cellular, immunological, and virological properties. We found that elevated and persistent HIV-1 pWT/BaL replication could be obtained only in MDMs grown in RPMI containing macrophage colony-stimulating factor (M-CSF). Interestingly, this MDM type was also most responsive to toll-like receptor stimulation. By contrast, all MDM types were activated to a comparable extent by intracellular DNA, and the macrophage serum-free medium-(Mac-SFM-)differentiated MDMs responded strongly to membrane fusion through expression of CXCL10. Finally, we found that HIV infection of RPMI/M-CSF-differentiated MDMs induced low-grade expression of two interferon-stimulated genes in some donors. In conclusion, our study demonstrates that the differentiation protocol used greatly influences the ability of MDMs to activate innate immune reactions and support HIV-1 replication. Paradoxically, the data show that the MDMs with the strongest innate immune response were also the most permissive for HIV-1 replication.